Biological Studies of some Ni(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Rani Sharma, Mamta (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes of formulae Ni[DCDTADH] (BF4)2 and Ni[DPDTADH](BF4)2 (where (DCDTADH) = 2,6-pyridine- dicarbonyl-dichloride-di-thio-diacetic acid dihydrazone and (DPDTADH) = 2,6-diacetyl pyridine di-thio-diacetic acid dihydrazone have been synthesized and characterized with the help of conductivity measurements, molecular weight determination, elemental studies and IR spectral analysis. The complexes have been found to possess octahedral geometry and have been found to be potentially active against a few bacteria and fungi and exhibit greater biocidal effect as compared to the ligand fragments and isolated metal ion.